Aplicação da técnica de ladrilhamento com polígonos regulares nos anos finais do ensino fundamental - Gumieri, Antonio Cláudio (2018)
This research presents a proposal of contextualizing Geometry teaching, for Elementary School (stag e II) students, exploring the concepts of regular polygons. First of all, some theoretical concepts about the subject were presented to the students, with the aim of simulating their interest for investigation in this Geometry field. To contextualize this knowledge, it was developed the idea of tessellation: students were presented to several parts in the format of different regular polygons, to use them to tile a plane. It was observed the students were interested to know more about the history of tessellation, as well as how could the tiles be arranged in different formats.